ANALISIS MEDIA PEMBELAJARAN FLASH CARD UNTUK MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK KELAS III SD NEGERI SENDEN TAHUN AJARAN 2025/2026 - Danang Saputra; Elinda Rizkasari; Sarafuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low learning motivation of students, which is shown through a lack of attention, activeness, and interest in participating in mathematics lessons. This study uses a qualitative approach with a descriptive research type. The research subjects include the principal, third-grade teachers, and third-grade students at SD Negeri Senden. Data collection techniques were done through observation, interviews, and documentation. Data validity used source triangulation and technique triangulation, while data analysis used the Miles and Huberman model, which includes data collection, data reduction, data presentation, and drawing conclusions. The results of the study show that using flashcard media can create learning that is more active, engaging, and enjoyable. Students' learning motivation increased, indicated by higher attention, activeness, courage to answer questions, enthusiasm for learning, and persistence in completing tasks. assignment. Thus, flash card learning media can be an effective alternative to increase elementary school students' motivation to learn mathematics.